SOVEREIGN CREDIT RATINGS AND POLICY IMPLICATIONS: CASE OF INDONESIA - Darwis, Firman
This research explores the effect of an additional variable proposed for use in Sovereign Credit Rating assessments by rating agencies, namely Credit Default Swap (CDS), as a measure of the probability of default in line with criticism of the predictive capacity of ratings using historical data and information. The research also aims to identify the main determinants of sovereign credit ratings in Indonesia and its peer group countries, namely the Philippines, Thailand, and Russia, from 2004 to 2022 by considering the indicators used as variables by the leading rating agencies. The methodology selection was based on suitability to the data, and the Vector Error Correction Model (VECM) was produced as the most appropriate methodology. There has yet to be any previous research that tested CDS as an indicator.